2018
DOI: 10.1177/0363546517746106
|View full text |Cite
|
Sign up to set email alerts
|

Lesion Size Does Not Predict Outcomes in Fresh Osteochondral Allograft Transplantation

Abstract: The size of the lesion, either absolute or relative, does not influence outcomes after OCA transplantation for isolated femoral condyle lesions of the knee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 22 publications
(29 reference statements)
1
39
0
2
Order By: Relevance
“…In fact, none of the patient- or lesion-associated parameters contributed significantly to the regression model of the KOOS Pain. This finding is in accordance with the results of a recently published study by Tirico and colleagues 36 in which the authors concluded that the size of the lesion had no influence on clinical outcomes in patients after OCA transplantation. While showing that patient sex has significant predictive value for postoperative KOOS Sport/Recreation, Tegner, and Lysholm scores, this study, in contrast to previous studies, 1 , 12 , 22 , 27 did not find any predictive value of patient age, BMI, OCA size, or patellar lesions for clinical outcomes at a minimum follow-up of 24 months.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, none of the patient- or lesion-associated parameters contributed significantly to the regression model of the KOOS Pain. This finding is in accordance with the results of a recently published study by Tirico and colleagues 36 in which the authors concluded that the size of the lesion had no influence on clinical outcomes in patients after OCA transplantation. While showing that patient sex has significant predictive value for postoperative KOOS Sport/Recreation, Tegner, and Lysholm scores, this study, in contrast to previous studies, 1 , 12 , 22 , 27 did not find any predictive value of patient age, BMI, OCA size, or patellar lesions for clinical outcomes at a minimum follow-up of 24 months.…”
Section: Discussionsupporting
confidence: 92%
“…Tirico et al [ 62 ] examined results of OCA by size of condylar defect in 156 knees from 1998 to 2014. The average graft area was 6.4 cm 2 , range 2.3–11.5 cm 2 .…”
Section: Evidence: Primary Studiesmentioning
confidence: 99%
“… 21 In a recent study, Tírico et al reported that the size of the lesion does not influence the outcomes of OCA for isolated femoral defects. 75 …”
Section: Complicationsmentioning
confidence: 99%